Aspirational Talk in CSR Communication: When Does it Turn Negative? - Lagemann, Pia Maria (2024)
Aspirational talk has seen growing interest in the field of corporate social responsibil-ity (CSR) communication since communicating about an organization's future inten-tions has the potential to move CSR programmes and the whole CSR field forward. However, much of society as well as the literature on CSR communication based in the functionalist perspective calls for alignment of talk and action and the practice of aspi-rational talk has been criticized for inviting hypocrisy and greenwashing accusations. This is especially the case for industries dealing with a lot of CSR challenges like the fashion industry. This thesis aims to explore what aspirational talk is and to under-stand when it turns negative, drawing from the hypocrisy and greenwashing litera-ture. Qualitative content analysis is employed to analyse 5 CSR reports from 2002-2022 from the H&M group. Findings showed that aspirational talk is a positively framed form of talk-action misalignment that appears in CSR communication as future-facing statements and idealized statements. Aspirational talk turns negative when the talk-action misalignment is perceived as behavioural inconsistency and interpreted as hy-pocrisy. Over the last 20 years, aspirational talk has been a regular element in the H&M group’s CSR reports and the amount of vague explorative statements has grown in comparison to more explicit and concrete types of aspirational talk. This thesis of-fers a conceptual model of how aspirational talk can lead to negative stakeholder reac-tions as well as empirical insights into how a company in the fashion industry engages in aspirational talk in its CSR reporting.